Socio-economic contributions of small-scale plantations in Ethiopia - Addisu Damtie, Yilebes (Array, 2019)
In order to enhance the attention given by farmers, government and concerned bodies, the socio-economic contributions of small-scale plantations should be studied. This study identified the socio-economic benefits of small-scale plantations in the Godera Woreda of Gambella Region, Ethiopia. Data were collected through questioners and key informant interviews from 208 farmers and 8 key informants. Descriptive statistics and a regression model were used to analyse the data. The results of the study revealed that of the average 1.72 ha of land possessed by small-scale farmers 0.81 ha was used for tree plantations. The main types of plantations were coffee, eucalyptus, banana and avocado. The mean annual production was 645 kg, 290 kg and 271 kg for coffee, banana and avocado, respectively. Small-scale farmers earned a mean of 4675.56 Birr from plantations which was 32.37 % of the total income. The Woreda government gained 365,022 Birr royalty payment during 2015/16.The regression results show income from plantations significantly affects the annual income of small-scale farmers (β = 0.436, p <0.01). Access to basic services, land use change, expenditures, population growth, employment opportunities, and migration are social changes supported by small-scale plantations. The availability of a favourable environment, extension service, land, and peace are opportunities of plantations. In contrast, challenges of small-scale plantations are disease, low prices for product, lack of improved plantation varieties, shortage of land, lack of demand, climate change and rainfall reduction, lack of government support, and high transportation costs. It is recommended to strengthen the small-scale plantations for better positive socio-economic contributions of the sector through supporting the opportunities and management of identified challenges.